Educational Assimilation of First-Generation and Second-Generation Immigrants in Germany - Gries, Thomas; Redlin, Margarete; Zehra, Moonum (Journal of International Migration and Integration)
Abstract Using data from the German Socio-Economic Panel for 1984–2018, we analyze the intergenerational education mobility of immigrants in Germany by identifying the determinants of differences in educational stocks for first- and second-generation immigrants in comparison to individuals without a migration background. Our results show that on average, first-generation immigrants have fewer years of schooling than native-born Germans and have a disproportionate share of lower educational qualifications. This gap is strongly driven by age at immigration, with immigration age and education revealing a nonlinear relationship. While the gap is relatively small among individuals who migrate at a young age, integrating in the school system at secondary school age leads to large disadvantages. Examining the educational mobility of immigrants in Germany, we identify an inter-generational catch-up in education. The gap in education between immigrants and natives is reduced for the second generation. Finally, we find that country of origin differences can account for much of the education gap. While immigrants with an ethnic background closer to the German language and culture show the best education outcomes, immigrants from Turkey, Italy, and other southern European countries and especially the group of war refugees from Syria, Afghanistan, Iraq and other MENA countries, have the lowest educational attainment.

Anthropogenic climate change: the impact of the global carbon budget - Redlin, Margarete; Gries, Thomas (Theoretical and Applied Climatology)
Abstract Using time series data for the period 1959–2015, our empirical analysis examines the simultaneous effects of the individual components of the global carbon budget on temperature. Specifically, we explore the possible effects of carbon emissions caused by fossil fuel combustion, cement production, land-use change emissions, and carbon sinks (here in terms of land sink and ocean sink) on climate change. The simultaneous inclusion of carbon emissions and carbon sinks allows us to look at the coexistent and opposing effects of the individual components of the carbon budget and thus provides a holistic perspective from which to explore the relationship between the global carbon budget and global warming. The results reveal a significant positive effect of carbon emissions on temperature for both fossil fuels emissions and emissions from land-use change, confirming previous results concerning carbon dioxide and temperature. Further, while ocean sink does not seem to have a significant effect, we identify a temperature-decreasing effect for land sink.

Gesellschaftliche Transformationen durch die Steigerung (popmusik)kultureller Teil-habe mittels innovativer Preiskonzepte – ein interdisziplinärer Literaturüberblick - Müller, Stefanie Jutta Marianne; Kundisch, Dennis

When do firms highlight their effective tax rate? - Flagmeier, Vanessa; Müller, Jens; Sureth-Sloane, Caren (Accounting and Business Research)
Keywords: Accounting; Finance

Development of a Strategic Controlling Concept - Fiedler, Moritz

Cost of Debt for Private Firms Revisited: Voluntary Audits as a Reflection of Risk - Ichev, Riste; Koren, Jernej; Kosi, Urska; Sitar Sustar, Katarina; Valentincic, Aljosa
This study examines the relation between voluntary audit and the cost of debt in private firms. We use a sample of 4,058 small private firms operating in the period 2006‐2017 that are not subject to mandatory audits. Firms decide for a voluntary audit of financial statements either because the economic setting in which they operate effectively forces them to do so (e.g., ownership complexity, export‐oriented supply chain, subsidiary status) or because firm fundamentals and/or financial reporting practices limit their access to financial debt, both reflected in earnings quality. We use these factors to model the decision for voluntary audit. In the outcome analyses, we find robust evidence that voluntary audits are associated with higher, rather than lower, interest rate by up to 3.0 percentage points. This effect is present regardless of the perceived audit quality (Big‐4 vs. non‐Big‐4), but is stronger for non‐Big‐4 audits where auditees have a stronger position relative to auditors. Audited firms’ earnings are less informative about future operating performance relative to unaudited counterparts. We conclude that voluntary audits facilitate access to financial debt for firms with higher risk that may otherwise have no access to this form of financing. The price paid is reflected in higher interest rates charged to firms with voluntary audits – firms with higher information and/or fundamental risk.
Keywords: private firms; voluntary audit; cost of debt; self‐selection bias; risk

Quo Vadis Conferences in the Business and Information Systems Engineering (BISE) Community After Covid - Leimeister, Jan Marco; Stieglitz, Stefan; Matzner, Martin; Kundisch, Dennis; Flath, Christoph; Röglinger, Maximilian

Kollusion durch Plattformen - der Einfluss von Tank-Apps auf den Preiswettbewerb von Tankstellen in Deutschland - Heinze, Erik

Big Data in Digital Markets - Challenges for Competition Policy to Protect Consumer Welfare - Rayhan, Shahi

Network Development of Low-Cost Carriers at German Airports - Joshan, Saeid

Plattformgestaltungen auf digitalen Märkten - eine Analyse der Wohlfahrtseffekte - Ajredini, Zurkani

Marktmachtmissbrauch digitaler Plattformen - eine Analyse anhand der zehnten Novelle des GWB - Kanne, Niklas

Marktmachtmissbrauch von Google – Eine wettbewerbspolitische Analyse - Klüppel, Pascal

COVID-19 Reporting and Willingness to Pay for Leisure Activities - Ortmann, Regina; Warkulat, Sonja; Krull, Sebastian; Klocke, Nina; Pelster, Matthias

Real effects of an international tax reform for MNEs - Ortmann, Regina; Simons, Dirk; Voeller, Dennis

Preisabsprachen in der Automobilindustrie - eine wettbewerbspolitische Analyse - Yigitbas , Osman

Facebooks digitale Währung - eine wettbewerbspolitische Analyse - Schulte, Marcel

Towards a Trust-Aware Item Recommendation System on a Graph Autoencoder with Attention Mechanism - Meydani, Elnaz; Düsing, Christoph; Trier, Matthias (Lecture Notes in Information Systems and Organisation)

PIVOT: A Parsimonious End-to-End Learning Framework for Valuing Player Actions in Handball using Tracking Data - Müller, Oliver; Caron, Matthew; Döring, Michael; Heuwinkel, Tim; Baumeister, Jochen (8th Workshop on Machine Learning and Data Mining for Sports Analytics (ECML PKDD 2021))
Over the last years, several approaches for the data-driven estimation of expected possession value (EPV) in basketball and association football (soccer) have been proposed. In this paper, we develop and evaluate PIVOT: the first such framework for team handball. Accounting for the fast-paced, dynamic nature and relative data scarcity of hand- ball, we propose a parsimonious end-to-end deep learning architecture that relies solely on tracking data. This efficient approach is capable of predicting the probability that a team will score within the near future given the fine-grained spatio-temporal distribution of all players and the ball over the last seconds of the game. Our experiments indicate that PIVOT is able to produce accurate and calibrated probability estimates, even when trained on a relatively small dataset. We also showcase two interactive applications of PIVOT for valuing actual and counterfactual player decisions and actions in real-time.
Keywords: expected possession value; handball; tracking data; time series classification; deep learning

To the Moon! Analyzing the Community of “Degenerates” Engaged in the Surge of the GME Stock - Caron, Matthew; Gulenko, Maryna; Müller, Oliver (42nd International Conference on Information Systems (ICIS 2021))
In early 2021, the finance world was taken by storm by the dramatic price surge of the GameStop Corp. stock. This rise is being, at least in part, attributed to a group of Redditors belonging to the now-famous r/wallstreetbets (WSB) subreddit group. In this work, we set out to address if user activity on the WSB subreddit is associated with the trading volume of the GME stock. Leveraging a unique dataset containing more than 4.9 million WSB posts and comments, we assert that user activity is associated with the trading volume of the GameStop stock. We further show that posts have a significantly higher predictive power than comments and are especially helpful for predicting unusually high trading volume. Lastly, as recent events have shown, we believe that these findings have implications for retail and institutional investors, trading platforms, and policymakers, as these can have disruptive potential.
Keywords: Retail investors; GameStop; Social Networks; Reddit; WallStreetBets

Towards a Trust-Aware Item Recommendation System on a Graph Autoencoder with Attention Mechanism - Meydani, Elnaz; Düsing, Christoph; Trier, Matthias (Innovation Through Information Systems: Volume II: A Collection of Latest Research on Technology Issues)

“I will survive”: Online streaming and the chart survival of music tracks - Kaimann, Daniel; Tanneberg, Ilka; Cox, Joe (Managerial and Decision Economics)

Die Aufteilung der Barentsseegebiete mithilfe des Adjusted Winner Verfahrens bei asymmetrischen Machtverhältnissen - N., N.

Versionisierung von Serviceleistungen auf Videoplattformen - N., N.

Kindergarten Allocation through Matching Mechanisms - N., N.

Faire Profitverteilung in Energienetzwerken - eine spieltheoretische Analyse von Microgrids - N., N.

"First-Party-Content" auf zweiseitigen Märkten - N., N.

Stability in many-to-many matchings with contracts - N., N.

Preissetzungsstrategien für Neuprodukte - N., N.

Co-opetition in Two-Sided Markets - N., N.

Matching mit Minderheiten - N., N.

Piracy and Visioning - N., N.

Revenue Sharing Contracts: Horizontale Koordination in der E-Commerce-Logistik - N., N.

Essays on Modeling Languages and Software Tools for Business Model Innovation: Theory and Empirical Evidence - Szopinski, Daniel

Dynamic Monopolistic Competition - Hoof, Simon (Journal of Optimization Theory and Applications)
I study a dynamic variant of the DixitâStiglitz (Am Econ Rev 67(3), 1977) model of monopolistic competition by introducing price stickiness Ã  la Fershtman and Kamien (Econometrica 55(5), 1987). The analysis is restricted to bounded quantity and price paths that fulfill the necessary conditions for an open-loop Nash equilibrium. I show that there exists a symmetric steady state and that its stability depends on the degree of product differentiation. When moving from complements to perfect substitutes, the steady state is either a locally asymptotically unstable (spiral) source, a stable (spiral) sink or a saddle point. I further apply the Hopf bifurcation theorem and prove the existence of limit cycles, when passing from a stable to an unstable steady state. Lastly, I provide a numerical example and show that there exists a stable limit cycle.

Der Einfluss der Besteuerung auf Managementanreize und die Nutzung von Bonusbanken - Dyck, Daniel (Junior Management Science)

Editorial: Schmalenbach IMPULSE: Will etwas in Bewegung setzen - Asenkerschbaumer, Stefan; Sureth-Sloane, Caren (Schmalenbach IMPULSE)

Selbstreguliertes Lernen im berufsschulischen Übergangssystem - Daniel-Söltenfuß, Desiree; Schwabl, Franziska (Zeitschrift für Berufs- und Wirtschaftspädagogik)
Keywords: Applied Mathematics; General Mathematics

Selbstreguliertes Lernen fördern - Lernen auf Distanz ermöglichen - Schwabl, Franziska; Daniel-Söltenfuß, Desiree (berufsbildung. Zeitschrift für Theorie-Praxis-Dialog)

Understanding cognitive decline in older ages: The role of health shocks - Schiele, Valentin; Schmitz, Hendrik
Individual cognitive functioning declines over time. We seek to understand how adverse physical health shocks in older ages contribute to this development. By use of event-study methods and data from the USA, England and several countries in Continental Europe we find evidence that health shocks lead to an immediate and persistent decline in cognitive functioning. This robust finding holds in all regions representing different health insurance systems and seems to be independent of underlying individual demographic characteristics such as sex and age. We also ask whether variables that are susceptible to policy action can reduce the negative consequences of a health shock. Our results suggest that neither compulsory education nor retirement regulations moderate the effects, thus emphasizing the importance of maintaining good physical health in old age for cognitive functioning.
Keywords: Cognitive decline; health shocks; retirement; education; event study

The dynamic and heterogeneous effects of retirement on cognitive decline - Schmitz, Hendrik; Westphal, Matthias
We study effects of retirement on cognitive abilities (up to ten years after retirement) using data from 21 countries in Continental Europe, England, and the US, and exploiting early-retirement thresholds for identification. For this purpose, combines event-study estimations with the marginal treatment effect framework to allow for effect heterogeneity. This helps to decompose event-study estimates into true medium-run effects of retirement and effects driven by differential retirement preferences. Our results suggest considerable negative effects of retirement on cognitive abilities. We also detect substantial effect heterogeneity: Those who retire as early as possible are not affected while those who retire later exhibit negative effects.
Keywords: Cognitive abilities; retirement; event study; marginal treatment effects

Exploring the paths towards service growth in manufacturing companies - Harrmann, L.; Böhm, Eva; Eggert, A. (2021 AMA Winter Academic Conference)

Engaging a product-focused sales force in solution selling: interplay of individual- and organizational-level conditions - Salonen, Anna; Terho, Harri; Böhm, Eva; Virtanen, Ari; Rajala, Risto (Journal of the Academy of Marketing Science)
Abstract This study explains how manufacturers tackle the critical managerial challenge of transforming a product-focused sales force to undertake solution selling. Through an application of configurational theory, the authors explain how individual and organizational conditions combine to determine salespeople’s engagement in solution selling. Multilevel, multisource data from the sales organization of a global supplier of building solutions represent input from salespeople ( N = 184), solution champions ( N = 23), and sales managers ( N = 26). A fuzzy set qualitative comparative analysis reveals no single, optimal way to overcome transformation challenges. Rather, consistent with prior research, solution selling requires certain types of salespeople, because value-based selling is a necessary condition for successful engagement. Beyond this foundational condition, a heterogeneous sales force can be engaged, as long as the organization provides appropriate support that is tailored to individual salespersons’ needs. The findings affirm that this viable support can come from either sales managers or solution champions.
Keywords: Marketing; Economics and Econometrics; Business and International Management

Online reviews generated through product testing: can more favorable reviews be enticed with free products? - Garnefeld, Ina; Krah, Tabea; Böhm, Eva; Gremler, Dwayne D. (Journal of the Academy of Marketing Science)
Abstract Online reviews have profound impacts on firm success in terms of sales volume and how much customers are willing to pay, yet firms remain highly dependent on customers’ voluntary contributions. A popular way to increase the number of online reviews is to use product testing programs, which offer participants free products in exchange for writing reviews. Firms that employ this practice generally hope to increase review quality and secure higher product rating scores. However, a qualitative study, experimental study, and multilevel analysis of a field study dataset of more than 200,000 online reviews by product testers combine to reveal that product testing programs do not necessarily generate higher quality reviews, nor better product ratings. Only in certain circumstances (e.g., higher priced products) does offering a product testing program generate these benefits for the firm. Therefore, companies should consider carefully if and when they want to offer product testing programs.
Keywords: Marketing; Economics and Econometrics; Business and International Management

Outcome-based contracting from the customers' perspective: A means-end chain analytical exploration - Schaefers, Tobias; Ruffer, Stefan; Böhm, Eva (Industrial Marketing Management)
Keywords: Marketing

Shared Leadership: Neue Studien für die Unternehmenspraxis - Krebs, Benjamin; Kabst, Rüdiger (PERSONALquartely)

HR-Manager als Intrapreneure - Wach, Bernhard; Krebs, Benjamin; Kabst, Rüdiger (HR-Trends 2021)

Passivität als Widerstand gegen die Macht der Verhältnisse? Melvilles Bartleby, the scrivener aus literaturwissenschaftlicher und ökonomischer Perspektive - Öhlschläger, Claudia; Schneider, Martin (Komparatistik heute)

CDS Investors’ Risk Perceptions of M&A Announcements - Hippert, Benjamin; Uhde, André
Merging a sample of 492 merger and acquisition (M&A) announcements from 284 acquiring firms across Europe and North America with data from 5-year single-name credit default swaps (CDSs) written on stock-listed acquiring firms between 2005 and 2018, the paper at hand empirically analyzes the CDS investors’ risk perceptions of M&A announcements using event study methodologies. As a baseline result, we provide evidence for significantly positive cumulative average abnormal CDS spread changes for both, European and North American acquirers suggesting that CDS investors perceive an increase in the acquiring firms’ credit risk exposures due to M&A announcements. Our baseline finding holds under several robustness checks, especially when controlling for the robustness of the empirical design. Moreover, results from a large variety of sensitivity analyses reveal a number of deal and firm characteristics that may explain why CDS investors from our sample expect an increase in the acquirers’ credit risk exposures due to forthcoming M&A transactions.
Keywords: credit default swaps; risk perception of CDS investors; mergers and acquisitions; event study

Determinants of CDS Trading on Major Banks - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias
This paper empirically investigates determinants of the outstanding net notional amount of credit default swaps (CDSs) contracts written on banks. We extend and complement the previous literature dealing with CDS trading by analyzing a comprehensive set of CDS tradingspecific, bank-fundamental, macroeconomic and bank-institutional determinants. We find that risk hedging clearly dominates an investor’s speculation and arbitrage motive, while the latter, however, exhibits the strongest impact on the outstanding net notional amount of bank CDSs. Furthermore, being classified as a G-SIB, being a constituent of the main CDS index and the equity trading volume may significantly explain changes in the outstanding CDS net notional on banks. The analysis at hand provides important implications for both academics and practitioners, since understanding the trading motives of bank CDS investors provides a deeper insight into the opaque CDS market.
Keywords: banking; outstanding CDS net notional; determinants of bank CDS trading